The Role of Side-Scrapers and Cortical Flakes in Late Acheulian Toolkits: Results of a Techno-functional Analysis from Revadim (Israel) - Venditti, Flavia; Barkai, Ran; Cesaro, Stella Nunzinate; Agam, Aviad (Lithic Technology, 2022)
Recent techno-functional studies of the lithic assemblage of Layer C3 in Late Acheulian Revadim (Israel) have demonstrated the variability in tool production and use in this layer. Here we present the results of a techno-functional and residue analysis of two central categories of artifacts found in Layer C3: side-scrapers and cortical flakes. We investigate the assumed functional link between side-scrapers and scraping activities and examine the question of whether cortical flakes were considered by the Revadim hominins as simple waste products or as useful tools. Our study applies an integrative and multidisciplinary methodology combining experimental archaeology, use-wear and residue analysis, and spectroscopic measurements. Our results show that side-scrapers were used for scraping and mixed activities, mostly on soft-medium and medium materials, while cortical flakes were occasionally used, mostly for cutting. Tool function reconstruction was supported by the morphological, elemental, and chemical characterization of extraordinarily well-preserved residues of animal origin, suggesting their use in butchery..
CRIS-Team WoS Importer:2022-02-18